Covalent Anchoring and Interfacial Reactions of Adsorbed Porphyrins on Rutile TiO2(110) - Wechsler, Daniel; Fernandez, Cynthia C.; Steinrück, Hans-Peter; Lytken, Ole; Williams, Federico J. (Journal of Physical Chemistry C, 2018)
Adsorption of 5-monocarboxyphenyl-10,15,20-triphenylporphyrin (MCTPP) to rutile TiO2(110) at room temperature produces molecules on the surface covalently anchored through the carboxylate group, coadsorbed with hydroxyl groups. At elevated temperatures, the free-base porphyrin molecules metalate on the surface, forming what we expect to be titanyl (Ti=O) porphyrin. The reaction is strongly coverage dependent with lower coverages metalating at lower temperatures, possibly caused by flat-lying molecules at low coverages being in closer proximity to the surface. This is in contrast to the behavior when exposed to Zn2+ ions in solution, where the coverage dependency is much less pronounced.